Hubungan Pengetahuan Dan Sikap Ibu Dengan Pemberian MP ASI Dini di Wilayah Kerja Puskesmas Jontor Kota Subulussalam Tahun 2022 - Eris Junaeti; Edy Marjuang Purba; Lidya Natalia Sinuhaji; Eka Purnamasari (LPPM STIKES Siti Hajar dan Insight Power, 2023)
The World Health Organization (2019) states that only 40% of babies in the world get exclusive breastfeeding, while 60% of other babies have received Complementary Food for Breast Milk (MP-ASI) when they are less than 6 months old. The purpose of this study was to analyze the relationship between knowledge and attitudes of mothers regarding early complementary breastfeeding in the Work Area of the Jontor Health Center, Subussalam City in 2022. This research used a quantitative approach with this type of observational study with a cross-sectional study. In this study, the population used was all mothers who had more babies who had passed the exclusive breastfeeding period in the Work Area of the Jontor Health Center, Subussalam City, namely 133. The sample in this study were mothers who had babies more than 6 months who were willing and available at the time of data collection. . The number of samples based on the sample formula is 48 people. Bivariate data analysis was carried out by statistical tests using chi-square. There is a significant relationship between the knowledge (p=0.022) and attitudes (p=0.006) of postpartum mothers and the provision of early MP-ASI in the Work Area of the Jontor Health Center in 2022. It is also hoped that health workers at the Jontor Health Center will be able to further increase public knowledge about MP -ASI and increasing its role in efforts to achieve exclusive breastfeeding through counseling, which can be carried out at village meetings, posyandu and counseling during pregnancy checks.Keywords: MP-ASI, knowledge, attitudes